Industrial training report: PETRONAS / Ardini Athirah Jamaluddin - Jamaluddin, Ardini Athirah (Faculty of Business and Management, 2025)
I worked on Change Management and Digital Branding & Communication during my 24-week internship with PETRONAS in the Adoption & Embedment (A&E) team. This experience provided me with the chance to develop a variety of skills that are essential for professional growth. This skill set includes communication, time management, collaborative teamwork, and creative thinking. I was required to have a comprehensive understanding of PETRONAS' business divisions, which include Upstream, Downstream, Gas & New Energy, and Project Delivery & Technology, as part of my internship. The development of insights into these processes was essential for the successful implementation of strategic planning and communication within the organization. The research offers a comprehensive analysis of PETRONAS, including a SWOT analysis that identifies its assets, weaknesses, opportunities, and threats, as well as recommendations for improving these areas. This report delineates strategies that are intended to enhance operational efficiency and resolve external concerns. I developed a more comprehensive comprehension of PETRONAS' strategic environment by utilizing the knowledge and skills I earned during my internship. It will be imperative to employ these insights in order to address substantial business challenges and enhance the company's international standing in the energy sector. This paper provides a comprehensive perspective on my tenure at PETRONAS by summarizing my internship experience, the skills I gained, an overview of PETRONAS' operations, and the principal insights from the SWOT analysis.